Speech Acts Uses in Persuasion and Deception in Marketing Discourse - Aziz, Shamal Ahmed Hama; Othman, Sara Kamal (Journal of Babylon University - Human Sciences, 2020)
The present study is an extract from an MA dissertation entitled "A Pragmatic Study of the Language of Deception in Marketing Discourse". Deception is one of the characteristics of human species. This is also true about language and language use in marketing discourse. The language of deception is an interesting subject in academics such as law, marketing and politics. There have been manyrese arches on the marketing discourse especially on the persuasion part of the discourse. Also, there have been studies on the language of advertising and marketing. Nevertheless, a pragmatic study of the language of deception in marketing discourse is not widespread especially studying the promotional aspects of deception in the fields of social media such as posts of Facebook, Twitter and YouTube Videos. The use of social media is increasing and this may result in an increase of deceptive language as well. Therefore, it is important to address this issue. One of the ways of dealing with it is concentrating on the communicative aspects of it. The speech act theory of Searle is used to analyse the corpus. The research starts with providing literature of marketing, persuasion, deception and it continues on explaining how speech acts used in those contexts. The collected data analysed are authentic taken from Facebook, Twitter and YouTube. The findings show that marketers apply mostly assertive speech acts to persuade and also avoid commitment. Also the use of commissive speech acts are not promising or guaranteeing, however it sounds promising but they can be denied. The paper concludes that speech act studies can be used to addressee deception in marketing discourse."